Step * of Lemma list_split_inverse

[T:Type]. ∀[f:(T List) ⟶ 𝔹]. ∀[L:T List]. ∀[LL:T List List]. ∀[X:T List].
  (concat(LL) X) ∈ (T List) supposing list_split(f;L) = <LL, X> ∈ (T List List × (T List))
BY
(Auto
   THEN MoveToConcl (-1)
   THEN GenConclAtAddr [1;2]
   THEN Auto
   THEN -3
   THEN -4
   THEN All Reduce
   THEN AutoSimpHyp Auto (-1)
   THEN -4
   THEN Auto) }


Latex:


Latex:
\mforall{}[T:Type].  \mforall{}[f:(T  List)  {}\mrightarrow{}  \mBbbB{}].  \mforall{}[L:T  List].  \mforall{}[LL:T  List  List].  \mforall{}[X:T  List].
    L  =  (concat(LL)  @  X)  supposing  list\_split(f;L)  =  <LL,  X>


By


Latex:
(Auto
  THEN  MoveToConcl  (-1)
  THEN  GenConclAtAddr  [1;2]
  THEN  Auto
  THEN  D  -3
  THEN  D  -4
  THEN  All  Reduce
  THEN  AutoSimpHyp  Auto  (-1)
  THEN  D  -4
  THEN  Auto)




Home Index